Multiplexed Cas9 targeting reveals genomic location effects and gRNA-based staggered breaks influencing mutation efficiency - Gisler, Santiago; Gonçalves, Joana P.; Akhtar, Waseem; de Jong, Johann; Pindyurin, Alexey V.; Wessels, Lodewyk F. A.; van Lohuizen, Maarten (Nature communications, 2019)
Understanding the impact of guide RNA (gRNA) and genomic locus on CRISPR-Cas9 activity is crucial to design effective gene editing assays. However, it is challenging to profile Cas9 activity in the endogenous cellular environment. Here we leverage our TRIP technology to integrate ~ 1k barcoded reporter genes in the genomes of mouse embryonic stem cells. We target the integrated reporters (IRs) using RNA-guided Cas9 and characterize induced mutations by sequencing. We report that gRNA-sequence and IR locus explain most variation in mutation efficiency. Predominant insertions of a gRNA-specific nucleotide are consistent with template-dependent repair of staggered DNA ends with 1-bp 5′ overhangs. We confirm that such staggered ends are induced by Cas9 in mouse pre-B cells. To explain observed insertions, we propose a model generating primarily blunt and occasionally staggered DNA ends. Mutation patterns indicate that gRNA-sequence controls the fraction of staggered ends, which could be used to optimize Cas9-based insertion efficiency. Designing effective genome engineering strategies requires an understanding of the impact that genomic locus has on CRISPR-Cas9 activity. Here the authors use TRIP integrations to profile editing outcomes genome-wide and observe that gRNA sequence influences the structure of the double strand break.